Intentionality, Conceptual Content, and Emotions - Peruzzo Júnior, Léo (Revista de Filosofia Aurora, 2019)
The present study aims at supporting the argument that emotions, unlike a physicalistic interpretation, cannot be reduced to the conceptual elements used in the communication or exteriorization process. The subject is based on two hypotheses: the first is that the relation between the issuance of an emotive content (emotion) and a possible mental representation presents a linguistic nature. In general terms, this means that an emotion, or the psychological content associated with it is based on the plot of other concepts. The second hypothesis is that it is not possible to refer to emotions without considering cognition from a semantic problem and, consequently, in the refusal of a realistic or anti-realistic posture in relation to the way the phenomena - internal and/or external to our consciousness - are referred. Thus, a conceptual model to understand emotions would be essential to settle the problem associated with ordinary language, realism, and the computational tendencies that comprehend the mental content in strictly syntactic terms.